(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
This essay explores some of the social implications of the transfer of tithing rights from the hands of the noble families to the communities in the Lombard mountains during the late Middle Ages. the aristocrats changed their social identity in the same period in which they were also taking on new fiscal and political positions in relation to the communities: before they had been men ‘outside the community’, who demanded tithes from the peasants but did not pay the tithes themselves; afterwards members of the communities, they shared these resources, but also these burdens, with their neighbors. even when they filled the seats of canons in the cathedral of Como or in the pievi (the main rural churches), in whose assets were included decimal incomes, or they took the positions of the bishopric rents collectors, they recognized the communities’ achievements, entrusting the latter with the rights of collection. A new customary arrangement – the possession of the tithing rights was in fact immovable and established fees stable over time – consolidated the communities’ conquests. When these conditions were altered, the communities took their opponents to court successfully. this process took place in a very different way both in the Alpine world and the Lombard valleys, but certainly marked a region in which the widespread aspiration of the european peasantry to manage tithes as a common good was fulfilled, changing but at the same time maintaining the traditional institutions and the legal framework, usually without open uprisings as happened elsewhere.